Globalisation Of Financial Reporting Standard Of Listed Companies In Asean Two: Malaysia And Singapore - Daw, Tin Hla; Abu Hassan, Md. Isa (Universiti Malaysia Sarawak (UNIMAS), 2015)
Malaysia and Singapore are the top two successful economies in the ASEAN region. They are converging their national accounting standards with the International Financial Reporting Standards (IFRSs) in an attempt to be more globalised. The globalisation of financial reporting standard is not just accounting focus but also for enhancing the quality and transparency of financial reporting of the firms in these countries. Investors and the other stakeholders rely on financial information reported by the firms on their websites to enable the information to access globally. This study focuses on the globalisation of financial reporting standards, corporate governance and transparency practice by the firms listed on Bursa Malaysia and Singapore. It is to analyse the level of financial reporting quality of the firms in compliance with the International Financial Reporting Standards (IFRS) in their annual reports by using disclosure analysis. Additionally, it determines the association between the financial reporting quality with IFRS compliance, and corporate governance and transparency practice of the firms listed on the main markets of Bursa Malaysia and main board of Singapore Stock Exchange (SGX), using multiple regression analysis. The finding of this study highlights the association of higher level of financial reporting quality with IFRS compliance of the firms, and their good corporate governance and transparency practice are positively associated in these two countries. This study also provides some opportunities to achieve sustainable convergence with the International Financial Reporting Standards of the firms by improving corporate governance and transparency in ASEAN countries.